Nanocomposite as well as preparation method and application thereof

The use of traditional fungicides is solved by the porphyrin metal organic framework and L-arginine in nanocomposites to produce reactive oxygen and nitric oxide under visible light and hydrogen peroxide conditions, combining to form peroxynitrite anionic radicals. The problem of large amount and bacterial resistance has achieved efficient bactericidal effect.

CN119455008APending Publication Date: 2025-02-18WUHAN POLYTECHNIC UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411475608.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing bacterial agents are used in large quantities and bacteria are prone to resistance, which limits the long-term development of bacterial technology.

Method used

Using a nanocomposite, including a porphyrin metal organic framework and loaded L-arginine, produces singlet oxygen by visible light excitation, and nitric oxide by L-arginine in the presence of hydrogen peroxide, further combining Produce peroxynitrite anionic radicals to enhance the bactericidal effect.

Benefits of technology

This nanocomplex has a strong bactericidal effect, is superior to traditional bactericidal agents, and reduces the inducing effect on bacterial resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455008A_ABST
    Figure CN119455008A_ABST
Patent Text Reader

Abstract

The invention discloses a nano-composite as well as a preparation method and application thereof, and relates to the technical field of sterilization, the nano-composite comprises a porphyrin metal organic framework and L-arginine loaded on the porphyrin metal organic framework. Wherein the porphyrin metal organic framework can generate singlet oxygen under the action of visible light so as to play a bactericidal role, and the L-arginine loaded on the porphyrin metal organic framework can be used as a nitric oxide generator so as to play a bactericidal role; in addition, the generated singlet oxygen and nitric oxide are further combined to generate peroxynitrite anion free radicals, so that strong oxidative damage can be caused, and the sterilization effect is further enhanced. Therefore, the nano-composite provided by the invention has a relatively strong bactericidal effect, and meanwhile, no antibiotics are added, so that the induction effect on bacterial drug resistance is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sterilization technology, and in particular to a nanocomposite and a preparation method and application thereof. Background Art

[0002] Foodborne pathogens refer to pathogenic bacteria that can cause diseases in humans and animals. These pathogens can survive in food and cause food to spoil through growth and metabolism. Some pathogens can secrete toxic substances, which can easily cause human diseases.

[0003] Antibiotics are widely used to control and treat infectious diseases caused by foodborne pathogens. However, with the frequent and improper use of antibiotics, more and more drug-resistant bacteria are emerging. Bacteria can not only develop antibiotic resistance on their own, but also transfer antibiotic resistance genes between bacteria through various mechanisms, making it possible for various drug-resistant strains to appear within a few years after new antibiotics are launched, increasing the research and development costs of medical drugs.

[0004] When using traditional disinfectants such as hydrogen peroxide, although the emergence of bacterial resistance is avoided, the disinfectant must reach a certain concentration to effectively kill microorganisms. These problems are not conducive to the long-term development of disinfection technology. Summary of the invention

[0005] The main purpose of the present invention is to provide a nanocomposite and a preparation method and application thereof, aiming to solve the problem in the prior art that a large amount of bactericide is used and bacteria are prone to drug resistance.

[0006] To achieve the above object, the present invention provides a nanocomposite comprising a porphyrin metal organic framework and L-arginine loaded on the porphyrin metal organic framework.

[0007] In one embodiment, the nanocomposite has a particle size of 100 to 200 nm; and / or,

[0008] The metal center of the porphyrin metal organic framework includes at least one of zirconium, cobalt, iron, manganese, copper, platinum and iridium; and / or,

[0009] The mass percentage of L-arginine in the nanocomposite is 6.45%.

[0010] The present invention also provides a method for preparing the nanocomposite, comprising the following steps:

[0011] The porphyrin metal organic framework, L-arginine and water are ultrasonically mixed, stirred in the dark, centrifuged to obtain solid matter, washed and dried to obtain the nanocomposite.

[0012] In one embodiment, in the step of ultrasonically mixing the porphyrin metal organic framework, L-arginine and water, stirring in the dark, centrifuging to obtain solid matter, washing, and drying to obtain the nanocomposite:

[0013] The mass ratio of the porphyrin metal organic framework, L-arginine and water is 1:5:1000; and / or,

[0014] The light-proof stirring time is 12 to 24 hours.

[0015] The present invention also provides the use of the nanocomposite or the nanocomposite prepared by the method for preparing the nanocomposite in sterilization.

[0016] In one embodiment, the application comprises the following steps:

[0017] The nanocomposite is added into a solution to be tested, a hydrogen peroxide solution is added, and light treatment is performed to obtain a treated solution to be tested.

[0018] In one embodiment, in the step of adding the nanocomposite to a test solution, adding a hydrogen peroxide solution, and performing light treatment to obtain a treated test solution:

[0019] The concentration of microorganisms in the solution to be tested is less than or equal to 10 8 CFU / mL,

[0020] After the nanocomplex is added into the test solution, the concentration of the nanocomplex in the test solution is 30-150 μg / mL.

[0021] In one embodiment, in the step of adding the nanocomposite to a test solution, adding a hydrogen peroxide solution, and performing light treatment to obtain a treated test solution:

[0022] The volume ratio of the hydrogen peroxide solution to the solution to be tested is 1:5000;

[0023] The final molar concentration of hydrogen peroxide in the hydrogen peroxide solution is 100 μM.

[0024] In one embodiment, in the step of adding the nanocomposite to a test solution, adding a hydrogen peroxide solution, and performing light treatment to obtain a treated test solution:

[0025] The light treatment includes light treatment using visible light, and the wavelength of the visible light is 400-700nm.

[0026] In one embodiment, in the step of adding the nanocomposite to a test solution, adding a hydrogen peroxide solution, and performing light treatment to obtain a treated test solution:

[0027] The light treatment time is 15 to 25 minutes.

[0028] The present invention provides a nanocomposite and a preparation method and application thereof, wherein the porphyrin metal organic framework can generate singlet oxygen under the action of visible light to exert a bactericidal effect, and the L-arginine loaded on the porphyrin metal organic framework can be used as a generator of nitric oxide to exert a bactericidal effect; in addition, the generated singlet oxygen and nitric oxide further combine to generate peroxynitrite anion free radicals that can cause strong oxidative damage, further enhancing the bactericidal effect. Therefore, the nanocomposite provided by the present invention has a strong bactericidal effect, which is better than that of traditional bactericides, and at the same time, no antibiotics are added, which reduces the induction of bacterial resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0030] Figure 1 (A) is a scanning electron microscope image of L-arg@PCN224 in Example 1 provided by the present invention, Figure 1 (B) is a transmission electron microscopy image of L-arg@PCN224 in Example 1 provided by the present invention;

[0031] Figure 2 (A) is a particle size distribution diagram of PCN224 provided by the present invention and L-arg@PCN224 in Example 1, Figure 2 (B) is the potential diagram of PCN224 provided by the present invention and L-arg@PCN224 in Example 1;

[0032] Figure 3 (A) is a graph showing the NO release amount of L-arg@PCN224 in Example 1 provided by the present invention in the presence of hydrogen peroxide over time. Figure 3 (B) is a graph showing the NO release of L-arg@PCN224 in Example 1 provided by the present invention in the presence of hydrogen peroxide as the concentration changes;

[0033] Figure 4 This is a result diagram of the release of reactive oxygen species (ROS) by L-arg@PCN224 in Example 1 provided by the present invention;

[0034] Figure 5(A) is a result diagram of the singlet oxygen release ability of L-arg@PCN224 in Example 1 provided by the present invention, Figure 5 (B) is an electron spin resonance (ESR) spectrum of L-arg@PCN224 in Example 1 provided by the present invention under dark conditions and visible light irradiation conditions;

[0035] Figure 6 This is a result diagram of the glutathione consumption ability of L-arg@PCN224 in Example 1 provided by the present invention;

[0036] Figure 7 (A) is a graph showing the inhibition effect of Escherichia coli in Comparative Examples 2 to 6 provided by the present invention, Figure 7 (B) is a graph showing the inhibitory effect of Staphylococcus aureus in Comparative Examples 2 to 6 provided by the present invention. Figure 7 (C) is a graph showing the inhibition effect of Escherichia coli in Comparative Examples 7 to 11 provided by the present invention, Figure 7 (D) is a graph showing the inhibitory effect of Staphylococcus aureus in Comparative Examples 7 to 11 provided by the present invention. Figure 7 (E) is a graph showing the inhibition effect of Escherichia coli in Examples 2 to 6 and Comparative Example 1 provided by the present invention, Figure 7 (F) is a graph showing the inhibitory effect of Staphylococcus aureus in Examples 2 to 6 and Comparative Example 1 provided by the present invention;

[0037] Figure 8 (A) is a typical colony image of Staphylococcus aureus under different treatment conditions provided by the present invention. Figure 8 (B) is a comparison chart of the colony counts of Staphylococcus aureus under different treatment conditions provided by the present invention. Figure 8 (C) is a typical colony image of Escherichia coli under different treatment conditions provided by the present invention. Figure 8 Middle (D) is a comparison chart of the colony counts of Escherichia coli under different treatment conditions provided by the present invention;

[0038] Fig. 9 Live / dead fluorescence images of Staphylococcus aureus and Escherichia coli under different treatment conditions provided by the present invention;

[0039] Fig.10 These are ROS fluorescence images of Staphylococcus aureus and Escherichia coli under different treatment conditions provided by the present invention.

[0040] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0041] To make the purpose, technical scheme and advantages of the embodiment of the present invention clearer, the technical scheme in the embodiment of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiment, it is carried out according to the normal conditions or the conditions recommended by the manufacturer. If the reagents or instruments used do not specify the manufacturer, they are all conventional products that can be purchased commercially. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes, taking "A and / or B" as an example, including scheme A, or scheme B, or schemes that A and B meet at the same time. In addition, the technical schemes between the various embodiments can be combined with each other, but must be based on the ability of ordinary technicians in the field to achieve. When the combination of technical solutions is contradictory or cannot be achieved, it should be considered that the combination of such technical solutions does not exist, and is not within the scope of protection required by the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present invention.

[0042] Foodborne pathogens refer to pathogenic bacteria that can cause diseases in humans and animals. These pathogens can survive in food and cause food to spoil through growth and metabolism. Some pathogens can secrete toxic substances, which can easily cause human diseases.

[0043] Antibiotics are widely used to control and treat infectious diseases caused by foodborne pathogens. However, with the frequent and improper use of antibiotics, more and more drug-resistant bacteria are emerging. Bacteria can not only develop antibiotic resistance on their own, but also transfer antibiotic resistance genes between bacteria through various mechanisms, making it possible for various drug-resistant strains to appear within a few years after new antibiotics are launched, increasing the research and development costs of medical drugs.

[0044] When using traditional disinfectants such as hydrogen peroxide, although the emergence of bacterial resistance is avoided, the disinfectant must reach a certain concentration to effectively kill microorganisms. These problems are not conducive to the long-term development of disinfection technology.

[0045] In view of this, the present invention provides a nanocomposite comprising a porphyrin metal organic framework and L-arginine loaded on the porphyrin metal organic framework.

[0046] In the technical solution of the present invention, the porphyrin metal organic framework can generate singlet oxygen under the action of visible light to exert a bactericidal effect, and the L-arginine loaded on the porphyrin metal organic framework can be used as a generator of nitric oxide to exert a bactericidal effect; in addition, the generated singlet oxygen and nitric oxide further combine to generate peroxynitrite anion free radicals, which can cause strong oxidative damage, further enhancing the bactericidal effect. Therefore, the nanocomposite provided by the present invention has a strong bactericidal effect, and at the same time, no antibiotics are added, which reduces the induction of bacterial resistance.

[0047] As a gas, nitric oxide (NO) has shown good effects in combating multi-drug resistant strains and can be used as an alternative to antibiotics. However, it has the following disadvantages: 1) NO is highly reactive and has a short half-life, making it difficult to achieve controlled release in traditional sterilization processes; 2) NO is very unstable in the air and will quickly react with oxygen to form nitrogen dioxide (NO2), and will also quickly convert into nitrate ions (NO2 - ), which makes NO difficult to store and transport, and also limits its use scenarios. In the nanocomposite provided in the present invention, L-arginine (L-arg) is a generator of NO, which means that L-arg can be converted into NO under the condition of hydrogen peroxide. Therefore, the nanocomposite of the present invention can achieve controllable release of NO through the conversion of L-arg under hydrogen peroxide conditions.

[0048] In some embodiments of the present invention, the diameter of the nanocomplex is 100-200 nm, and the particle size may be 100 nm, 150 nm or 200 nm. The particle size within a suitable range helps the nanocomplex to pass through the biological barrier and exert a bactericidal effect.

[0049] In some embodiments of the present invention, the metal center of the porphyrin metal organic framework includes at least one of zirconium, cobalt, iron, manganese, copper, platinum, and iridium. That is, the metal center of the porphyrin metal organic framework (MOFs) can be any one of zirconium, cobalt, iron, manganese, copper, platinum, and iridium, or two or more of zirconium, cobalt, iron, manganese, copper, platinum, and iridium, all within the protection scope of the present invention. When the metal center of the porphyrin metal organic framework has multiple types of metals, it indicates that different metal ions are integrated into different positions of the same framework, or are combined with porphyrin ligands in the same coordination unit. The synthesis of multimetallic porphyrin MOFs can be achieved by sequential addition method, co-mixing method, post-modification method, etc. When the metal center of porphyrin MOFs is zirconium, it is called PCN224, and the organic ligand is tetracarboxylphenyl porphyrin. The porphyrin MOFs can produce active oxygen under the action of visible light and play a bactericidal effect. It should be noted that the porphyrin metal organic framework is a nano-scale granular material.

[0050] In some embodiments of the present invention, the mass percentage of L-arginine in the nanocomposite is 6.45%. The mass percentage of 6.45% can ensure the structural integrity and stability of porphyrin MOFs, while controlling the release rate of L-arginine, thereby regulating the generation rate of NO.

[0051] The present invention also provides a method for preparing the nanocomposite, comprising the following steps: ultrasonically mixing the porphyrin metal organic framework, L-arginine and water, stirring in the dark, centrifuging to obtain the solid matter, washing, and drying to obtain the nanocomposite. The mixed solution needs to be stirred in the dark. The light-proof operation is to prevent the porphyrin MOFs and L-arginine from decomposing due to light, especially the porphyrin structure is sensitive to light and is prone to photolysis. The method for preparing the nanocomposite provided by the present invention is simple and easy to operate, and has little pollution to the environment.

[0052] In some embodiments of the present invention, in the step of ultrasonically mixing the porphyrin metal organic framework, L-arginine and water, stirring in the dark, centrifuging to obtain the solid matter, washing, and drying to obtain the nanocomposite: the mass ratio of the porphyrin metal organic framework, L-arginine and water is 1:5:1000; and / or, the time of stirring in the dark is 12 to 24 hours. The mass ratio of 1:5:1000 can ensure that the structural integrity and stability of the porphyrin MOFs in the nanocomposite are good, while ensuring a high L-arg loading.

[0053] The light-proof stirring time can be 12 hours, 20 hours or 24 hours. The light-proof stirring time within a suitable range can ensure that the porphyrin metal organic framework and L-arginine are fully contacted to form a nanocomposite.

[0054] Commonly used antibiotics, also known as antibiotics and antibacterial drugs, have no adverse effects on human or animal cells and are substances that kill or inhibit the growth and reproduction of microorganisms. Antibiotics are produced by fungi, bacteria, etc. during their growth process, and can also be manufactured by artificial modification, semi-synthesis or synthesis. Antibiotics can selectively act on the links of the DNA, RNA and protein synthesis systems of bacterial cells, thereby interfering with cell metabolism, hindering life activities or stopping growth, and even causing cell death. The mechanism of action of antibiotics can be divided into four categories: 1) hindering the synthesis of bacterial cell walls. When the synthesis of bacterial cell walls is blocked, they will swell in a low osmotic pressure environment, eventually rupture and die; 2) interacting with bacterial cell membranes will enhance the permeability of bacterial cell membranes and open ion channels on the membrane, causing useful substances inside the bacteria to leak out of the bacteria or electrolyte imbalance and death; 3) bacterial ribosomes or their reaction substrates (such as tRNA, mRNA) are disturbed, which will inhibit protein synthesis. This means that the structural proteins and enzymes necessary for cell survival cannot be synthesized, and bacteria cannot survive; 4) when the replication and transcription process of bacterial DNA is blocked, cell division and reproduction will be inhibited. If DNA cannot replicate, bacterial cells cannot proliferate; if DNA cannot be transcribed into mRNA, the subsequent protein synthesis process will also be blocked, eventually leading to bacterial death. However, with the frequent and improper use of antibiotics, more and more drug-resistant bacteria are emerging. Bacteria can not only produce antibiotic resistance on their own, but also have the ability to transmit antibiotic resistance genes between bacteria through various mechanisms, so that various drug-resistant strains may appear within a few years after new antibiotics are listed, seriously threatening human survival. At present, the problem of bacterial resistance is solved by the following two ways: discovering new antibiotics to inhibit bacteria and modifying and transforming existing antibacterial drugs. However, it takes a long time to develop new antibiotics, the therapeutic effect cannot be guaranteed, and it is difficult to conduct synchronous research with bacterial resistance. The present invention provides a nanocomposite or a nanocomposite prepared by a method for preparing the nanocomposite for use in sterilization. The nanocomposite and the method for preparing the nanocomposite have all the above-mentioned technical effects, which will not be repeated here. It should be noted that the nanocomposite provided by the present invention can be used in the fields of food preservation and medical care, and can be made into food packaging or wound dressings to exert a sterilizing effect.

[0055] In some embodiments of the present invention, the application includes the following steps: adding the nanocomplex to a solution to be tested, adding a hydrogen peroxide solution, and performing light treatment to obtain a treated solution to be tested.

[0056] In the technical scheme of the present invention, under the condition of light treatment, the nanocomposite releases L-arg, and the porphyrin metal organic framework absorbs light energy, so that the electrons in the porphyrin structure transition from the ground state to the excited state. The excited porphyrin MOFs can be used as a photocatalyst to produce reactive oxygen species mainly composed of singlet oxygen in the test solution. The generated reactive oxygen can oxidize and damage proteins and DNA, hinder cell division and reduction, destroy the antioxidant defense system of bacteria, and cause cell damage, and ultimately lead to cell death; at the same time, in the presence of hydrogen peroxide, L-arg generates NO, which can play a bactericidal role by interfering with bacterial cell metabolism, inactivating protein function and promoting lipid peroxidation; in addition, according to literature reports, NO will generate peroxynitrite anion (ONOO-) in the presence of ROS. ONOO- is a kind of active free radical that can cause strong oxidative damage, such as attacking DNA, leading to base oxidation, formation of depurine / apyrimidinic sites, and ultimately causing DNA double-strand breaks, thereby inhibiting the replication and proliferation of microorganisms. Therefore, the nanocomposite of the present invention can simultaneously exert the synergistic antibacterial effects of photodynamic therapy (PDT), NO bactericidal, and ONOO-bactericidal.

[0057] In some embodiments of the present invention, in the step of adding the nanocomposite to the test solution, adding the hydrogen peroxide solution, and performing light treatment to obtain the treated test solution: the concentration of microorganisms in the test solution is less than or equal to 10 8 CFU / mL; after the nanocomplex is added to the test solution, the concentration of the nanocomplex in the test solution is 30-150 μg / mL.

[0058] The concentration of microorganisms in the test solution can be 10 8 CFU / mL, 10 7 CFU / mL or even smaller, the concentration of microorganisms within the appropriate range can ensure a better sterilization effect.

[0059] After the nanocomplex is added to the test solution, the concentration of the nanocomplex in the test solution is 30 μg / mL, 55 μg / mL, 95 μg / mL, 135 μg / mL or 150 μg / mL, and the concentration within the appropriate range can ensure the activity and bactericidal effect of the nanocomplex.

[0060] In some embodiments of the present invention, in the step of adding the nanocomposite to the solution to be tested, adding the hydrogen peroxide solution, and performing light treatment to obtain the treated solution to be tested: the volume ratio of the hydrogen peroxide solution to the solution to be tested is 1:5000; the final concentration of hydrogen peroxide in the hydrogen peroxide solution is 100 μM. The volume ratio of the hydrogen peroxide solution to the solution to be tested is 1:5000, which can ensure that L-arg releases more NO, and the final concentration of hydrogen peroxide in the hydrogen peroxide solution is 100 μM, which can ensure that L-arg releases more NO in a shorter time.

[0061] In some embodiments of the present invention, in the step of adding the nanocomposite to the test solution, adding the hydrogen peroxide solution, and performing light treatment to obtain the treated test solution: the light treatment includes using visible light for light treatment, and the wavelength of the visible light is 400-700nm. The wavelength of the visible light can be 400nm, 500nm, 600nm or 700nm. The wavelength of the visible light in the appropriate range can ensure that the photocatalytic activity of the nanocomposite is high, the photocatalytic efficiency is fast, and more ROS can be generated in a shorter time.

[0062] In some embodiments of the present invention, in the step of adding the nanocomposite to the test solution, adding the hydrogen peroxide solution, and performing light treatment to obtain the treated test solution: the light treatment time is 15 to 25 minutes. The light treatment time can be 15 minutes, 20 minutes or 25 minutes. The light treatment time within a suitable range can ensure that the nanocomposite produces more ROS.

[0063] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and drawings. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0064] Example 1

[0065] A method for preparing a nanocomposite comprises the following steps:

[0066] (1) Preparation of PCN224: First, 100 mg of 5,10,15,20-tetrakis(p-carboxyphenyl)porphyrin (TCPP), 300 mg of zirconium chloride octahydrate (ZrOCl2·8H2O) and 2.8 g of benzoic acid were dissolved in 100 mL of N,N-dimethylformamide (DMF), mixed and transferred into a clean, anhydrous flask. The solution was then placed in an oil bath at 90°C and heated at 300 rpm with stirring, reacted for 5 hours in the dark and condensed under reflux. After the reaction was completed, it was cooled to room temperature, centrifuged (10,000 rpm, 30 min) and washed three times with DMF to obtain a purple solid, namely PCN224 (also referred to as PCN).

[0067] (2) Preparation of nanocomposite L-arg@PCN: 10 mg PCN224 and 50 mg L-Arg were dissolved in 10 mL deionized water, ultrasonically mixed and stirred overnight (12 h) in the dark, centrifuged (10,000 rpm, 15 min) and washed twice with deionized water, and finally dried in an oven at 60 °C to obtain a solid product L-arg@PCN (also referred to as L-arg@PCN224), i.e., a nanocomposite.

[0068] Example 2

[0069] This embodiment provides a sterilization method using the nanocomposite provided by the technical solution of the present invention. The method comprises the following steps:

[0070] The nanocomposite L-arg@PCN prepared in Example 1 was added to the Staphylococcus aureus solution and the Escherichia coli solution, respectively, so that the concentration of L-arg@PCN was 30 μg / mL, and then a hydrogen peroxide solution was added (the final concentration of hydrogen peroxide in the hydrogen peroxide solution was 100 μM), and 633 nm light treatment was performed for 20 minutes to obtain treated Staphylococcus aureus solutions and Escherichia coli solutions.

[0071] Embodiments 3 to 6

[0072] Examples 3 to 6 are similar to Example 2, except that the concentrations of L-arg@PCN are 60, 90, 120, and 150 μg / mL, respectively.

[0073] Comparative Example 1

[0074] The difference between Comparative Example 1 and Example 2 is that the concentration of L-arg@PCN is 0 μg / mL and H2O2 is not added.

[0075] Comparative Example 2

[0076] The difference between Comparative Example 2 and Example 2 is that no H2O2 solution is added and no light treatment is performed.

[0077] Comparative Examples 3 to 6

[0078] Comparative Examples 3 to 6 are similar to Comparative Example 2, except that the concentrations of L-arg@PCN are 60, 90, 120, and 150 μg / mL, respectively.

[0079] Comparative Example 7

[0080] Compared with Example 2, Comparative Example 7 is different in that L-arg@PCN is replaced by PCN224, the concentration of PCN224 is 28 μg / mL, and no H2O2 solution is added.

[0081] Comparative Examples 8 to 11

[0082] Comparative Examples 8 to 11 are similar to Comparative Example 7, except that the concentrations of PCN224 are 56, 84, 112, and 148 μg / mL, respectively.

[0083] Comparative Example 12

[0084] The difference between Comparative Example 12 and Example 2 is that there is only H2O2.

[0085] Performance Testing

[0086] The loading rate of L-arg in the nanocomposite prepared in Example 1 was measured, and the measuring method was as follows: the supernatant after centrifugal washing twice during the synthesis of L-arg@PCN224 was collected and mixed evenly, and 1 mL of NaOH solution, naphthol n-propanol solution and diacetyl n-propanol solution were added to the test tube in sequence, and then 1 μL of 5 mg / mL, 10 mg / mL, 15 mg / mL, 20 mg / mL, 25 mg / mL, 30 mg / mL of L-arg standard solution and supernatant sample solution were added, shaken and evenly mixed, and the OD value at 540 nm of the reaction solution was measured after heating in a water bath for a certain period of time. Then the OD value was used as the ordinate and 5 to 30 mg / mL was used as the abscissa to draw a graph, and then the regression curve was obtained, and the OD value obtained by the sample measurement was brought into the regression curve to obtain the L-arg concentration in the supernatant. The loading amount in L-arg@PCN224 can be obtained by the following formula:

[0087] Loading amount = (L-arg added during synthesis - L-arg concentration in supernatant × supernatant volume) / mass of L-arg@PCN224.

[0088] The results show that the loading efficiency of L-arg in L-arg@PCN224 is 6.45%.

[0089] The microscopic morphology, particle size and potential of the nanocomposite prepared in Example 1 were characterized. Figure 1 and Figure 2 shown.

[0090] Figure 1 (A) is a scanning electron microscope image of L-arg@PCN224 prepared in Example 1. Figure 1 (B) is a transmission electron micrograph of L-arg@PCN224 in Example 1. It can be seen that the prepared nanoparticles are relatively spherical.

[0091] Figure 2(A) is a particle size distribution diagram of PCN224 and L-arg@PCN224 in Example 1 detected by dynamic light scattering. The results show that the particle size distribution range of L-arg@PCN224 is mainly 150-200nm, which is slightly larger than PCN224, indicating that L-arg is successfully loaded on PCN224.

[0092] Figure 2 (B) is the potential diagram of PCN224 and L-arg@PCN224 in Example 1. The results show that the Zeta potentials of L-arg, PCN224 and L-arg@PCN are -49.02 mV, 32.33 mV and -24.48 mV, respectively. The potential of PCN224 changed before and after loading. The change in potential also shows that L-arg successfully modified PCN224.

[0093] The ability of the nanocomposite prepared in Example 1 to release NO was tested. The test method was as follows: H2O2 was added to L-arg@PCN solutions with concentrations of 30, 60, 90, 120 and 150 μg / mL (9 mg of the nanocomposite was dissolved in 30 mL of pure water to obtain a 300 μg / mL solution, which was mixed with an equal volume of bacterial solution) under light-proof conditions to make the final concentration of 100 μM, and the NO release concentration was quantitatively determined using a nitric oxide detection kit. The treatment with only L-arg@PCN solution added without H2O2 was used as the control group. The results are shown in FIG. Figure 3 shown.

[0094] Figure 3 (A) is a graph showing the NO release of L-arg@PCN224 in Example 1 in the presence of hydrogen peroxide over time. The results show that the NO release increases with time, and the NO release tends to stabilize after 8 minutes, at which time the NO release is about 6.65 μM. However, almost no NO release was detected in the control group. This indicates that L-arg@PCN224 has the ability to release NO in the presence of H2O2.

[0095] Figure 3 (B) is a graph of NO release from L-arg@PCN224 in Example 1 in the presence of hydrogen peroxide as the concentration changes. The results show that the NO release is also related to the concentration of L-arg@PCN224. In the presence of H2O2, the higher the concentration of L-arg@PCN224, the greater the NO release. Therefore, L-arg@PCN224 has a concentration-dependent effect and has the ability to release NO in the presence of H2O2.

[0096] ROS can produce oxidative effects on cell membrane structures, nucleic acids and protein molecules, causing structural and functional disorders. Increased ROS can lead to oxidative stress responses in the body and cause cell damage. The ability of the nanocomplex prepared in Example 1 to release ROS was tested. The test method was as follows: 2',7'-dichlorodihydrofluorescein diacetate (DCFH-DA) was used as a sensor, and the generation of ROS was detected by fluorescence spectroscopy. Phosphate buffered saline (PBS) was used as a control group. The test results are shown in Figure 2. Figure 4 shown.

[0097] Depend on Figure 4 It can be seen that the fluorescence intensity of the control group did not change much. However, the fluorescence intensity of the L-arg@PCN group increased significantly with the extension of the irradiation time, indicating that L-arg@PCN has the ability to produce ROS under visible light irradiation, so it can damage cells and kill bacteria.

[0098] Singlet oxygen is a general term for the paramagnetic state of molecular oxygen. It is a type of reactive oxygen and can be formed in many free radical reactions. Singlet oxygen has a much higher reactivity than ordinary oxygen because its electrons are freed from spin restrictions. It is a very unstable form of oxygen. Cell membranes, mitochondria and other structures are most sensitive to singlet oxygen. Singlet oxygen can interact with a variety of biological macromolecules in cells and can cause damage to the cell membrane system by binding to molecules. The ability of the nanocomplex prepared in Example 1 to release singlet oxygen was tested. The test method was: using SOSG as a sensor, fluorescence spectroscopy was used to detect the generation of singlet oxygen, and PBS treatment and SOSG treatment were used as control groups. The test results Figure 5 As shown in (A).

[0099] Depend on Figure 5 As shown in (A), the release of singlet oxygen in the L-arg@PCN group continued to increase over time, and the release amount almost stopped increasing at 240s. The singlet oxygen content in the PBS group and the SOSG group was close to zero, with almost no release.

[0100] ESR is an analytical test method to determine what kind of free radicals are generated in the photocatalytic process. Its principle is to rely on the spin resonance spectrum of single-electron substances to identify the types of free radicals in the photocatalytic reaction. The electron spin resonance of the nanocomposite prepared in Example 1 was tested under dark conditions and visible light irradiation conditions. The results are as follows: Figure 5 As shown in (B).

[0101] Depend on Figure 5As can be seen in (B), L-arg / PCN shows a characteristic peak of singlet oxygen under visible light irradiation (red line), while L-arg / PCN does not show a characteristic peak under light-protected conditions (black line), indicating that the prepared nanomaterial L-arg / PCN has the ability to produce singlet oxygen under visible light irradiation, thereby causing damage to cells and killing bacteria.

[0102] Glutathione plays an important role in the bacterial antioxidant defense system, preventing free radicals from damaging cellular components and has become a marker for detecting cellular oxidative stress. Figure 6 As shown, Comparative Example 1 (H2O2 group) has almost no effect on oxidizing glutathione, while Comparative Example 6 (L-arg / PCN group) and Comparative Example 11 (PCN+L group) induce glutathione loss rates of 22.64% and 26.47%, respectively, and Example 6 (L-arg / PCN+H2O2+L group) induces glutathione loss rate of 81.17%, which is much higher than that of other groups. This shows that L-arg / PCN has a strong ability to oxidize glutathione when H2O2 is added under visible light irradiation, which is beneficial for the synthetic material to destroy the antioxidant defense system of bacterial cells, thereby damaging the bacterial cells and killing the bacteria.

[0103] The antibacterial effects of Examples 2 to 6 and Comparative Examples 1 to 12 were tested.

[0104] (1) In vitro antibacterial test

[0105] When the test solution is Staphylococcus aureus and Escherichia coli, the antibacterial effects of Examples 2 to 6 and Comparative Examples 1 to 12 are tested. The results are as follows: Figure 7 shown.

[0106] Depend on Figure 7 As shown in (F), compared with Comparative Example 1, the growth of Staphylococcus aureus was significantly delayed with the increase of the concentration of L-arg / PCN+H2O2+L in Examples 2 to 6, especially when the concentration was 150 μg / mL, the growth curve was close to the horizontal line, indicating that the growth of Staphylococcus aureus was greatly inhibited. Figure 7 As shown in (D), in Comparative Examples 2 to 6 (PCN+L group), the growth of Staphylococcus aureus was also delayed as the PCN concentration increased, but at the same concentration, the growth delay was not as obvious as that of Examples 2 to 6 (L-arg / PCN+H2O2+L group), indicating that there was a small amount of bacterial proliferation in this group. Figure 7 As shown in (B), the growth curves of Staphylococcus aureus at different concentrations of L-arg / PCN in Comparative Examples 2 to 6 are similar to those in Comparative Example 1 (0 μg / mL), indicating that the bacteria proliferated in large quantities and the inhibitory effect was not obvious. A similar phenomenon was also found in Escherichia coli [ Figure 7 Middle (A), Figure 7 Middle (C) and Figure 7 (E)]. These differences can be attributed to the following: in comparative examples 2 to 6 (L-arg / PCN group), L-arg / PCN does not produce ROS and NO under light-proof conditions, and bacterial growth is only affected by L-arg / PCN, with limited antibacterial effect; in comparative examples 7 to 11 (PCN+L group), PCN224 produces ROS and kills bacteria under visible light irradiation, with a good antibacterial effect. In Examples 2 to 6 (L-arg / PCN+H2O2+L group), L-arg / PCN produces ROS and releases L-Arg under visible light irradiation, L-Arg can generate NO under H2O2 conditions, and NO will generate peroxynitrite anion ONOO- under the condition of ROS presence, ONOO- is a free radical with active properties, which can cause strong oxidative damage. Therefore, the realization of L-arg / PCN+H2O2+L sterilization is the synergistic effect of ROS, NO and ONOO-, and its sterilization effect is better than that of using PCN224 or NO alone.

[0107] The plate count method was used to further verify the antibacterial effects of Examples 2 to 6 and Comparative Examples 1 to 12. The plate count method steps were as follows: Staphylococcus aureus and Escherichia coli were cultured overnight until the concentration of the bacteria reached 10 8 CFU / mL, and then dilute the bacterial solution to 10 5 CFU / mL Take 100 μL as the Staphylococcus aureus solution and Escherichia coli solution in Examples 2 to 6 and Comparative Examples 1 to 12, respectively. After the above Staphylococcus aureus solution and Escherichia coli solution are processed in Examples 2 to 6 and Comparative Examples 1 to 12, a bacterial suspension is obtained. Dilute the bacterial suspension, and then apply the diluted suspension (20 μL) on the LB agar plate, and then culture it at 37°C for 12 hours. In addition, PBS-treated bacteria are used as the control. Finally, the number of colonies (CFU) on the agar plate is counted and the antibacterial effect is evaluated according to the following formula:

[0108] Survival rate (%) = CFU (experimental group) / CFU (control group) × 100%

[0109] Among them, CFU (experimental group) is the number of colonies in the material treatment group, and CFU (control group) is the number of colonies in the control group. Figure 8 shown.

[0110] Figure 8 where a1, a2, a3, a4 and a5 correspond to Figure 7 The different addition concentrations in the , and a1<a2<a3<a4<a5. Figure 8As shown in (A), with the increase of material concentration, the number of colonies in Comparative Examples 2 to 6 (L-arg / PCN group) remained almost unchanged, while the number of colonies in Comparative Examples 7 to 11 (PCN+L group) and Examples 2 to 6 (L-arg / PCN+H2O2+L group) became less and less. In addition, the change in Examples 7 to 11 (L-arg / PCN+H2O2+L group) was the most significant compared with other groups, especially when the concentration was 150 μg / mL [ Figure 8 In (A) a5], only a small amount of Staphylococcus aureus grew on the plate. Figure 8 As shown in (C), E. coli colonies also exhibit similar phenomena. Figure 8 It can be seen in (B) that the survival rates of Staphylococcus aureus in Comparative Examples 7 to 11 (PCN+L group) and Examples 2 to 6 (L-arg / PCN+H2O2+L group) continue to decrease with the increasing concentration of the antibacterial agent, and the survival rate in Examples 2 to 6 (L-arg / PCN+H2O2+L group) decreases most significantly compared with other groups. When the concentration is 150 μg / mL, the survival rate of Staphylococcus aureus is lower than that of the control group. At this time, the survival rates of Comparative Example 6 (L-arg / PCN group), Comparative Example 11 (PCN+L group) and Example 6 (L-arg / PCN+H2O2+L group) are 98.84%, 8.93% and 3.15%, respectively. Figure 8 As shown in (D), the effect of the antibacterial test of Escherichia coli is similar to that of Staphylococcus aureus. When the concentration is 150 μg / mL, the survival rates of Comparative Example 6 (L-arg / PCN group), Comparative Example 11 (PCN+L group) and Example 6 (L-arg / PCN+H2O2+L group) are 100%, 4.82% and 1.44%, respectively. This is because the L-arg / PCN+H2O2+L group has a synergistic antibacterial effect, which is consistent with the above-mentioned bacterial growth kinetics results.

[0111] The fluorescence intensity of Staphylococcus aureus and Escherichia coli in Example 6, Comparative Example 1, Comparative Example 6, Comparative Example 11 and Comparative Example 12 was measured by fluorescent live / dead cell staining experiment to further determine the synergistic antibacterial activity of the L-arg / PCN+H2O2+L group. The PBS treatment was used as the control group. The results are shown in FIG. Fig. 9 shown.

[0112] In fluorescent live / dead staining experiments, PI dye can only pass through damaged cell membranes and bind to DNA to emit red fluorescence; STYO 9 can stain all cells and present green fluorescence. Fig. 9It can be seen that there is a large amount of green fluorescence in Comparative Example 1 (Control group), indicating that most of the cells of Staphylococcus aureus and Escherichia coli are intact. Similar phenomena are also seen in Comparative Example 12 (H2O2 group) and Comparative Example 6 (L-arg / PCN group), indicating that H2O2 and L-arg / PCN treatment under light-proof conditions have no effect on the cell membranes of most Staphylococcus aureus and Escherichia coli. In contrast, Comparative Example 11 (PCN+L group) exhibits a strong red fluorescence, indicating that some of the Staphylococcus aureus and Escherichia coli are damaged. A large amount of red fluorescence is shown in Example 6 (L-arg / PCN+H2O2+L group), indicating that the cell membranes of most Staphylococcus aureus and Escherichia coli are destroyed and the bacteria die. It is further confirmed that the L-arg / PCN+H2O2+L group has a synergistic antibacterial effect.

[0113] The ROS fluorescence intensity of Staphylococcus aureus and Escherichia coli in Example 6, Comparative Example 1, Comparative Example 6, Comparative Example 11 and Comparative Example 12 was measured. The test method is as follows: DCFH-DA is used as a probe. DCFH-DA itself does not have spontaneous fluorescence, but has cell membrane permeability and can freely enter the cell. In the cell, it can be hydrolyzed by esterase to generate DCFH. DCFH reacts with ROS to generate a fluorescent product (green). Therefore, the generation of ROS can be detected by fluorescence microscopy. The results are shown in FIG. Fig.10 shown.

[0114] Depend on Fig.10 It can be seen that the bacteria in Example 6 (L-arg / PCN+H2O2+L group) showed a large number of green fluorescence spots, while Comparative Example 6 (L-arg / PCN group) and Comparative Example 11 (PCN+L group) showed a small amount of green fluorescence, and almost no green fluorescence spots were observed in Comparative Example 1 (control group) and Comparative Example 12 (H2O2 group), which indicates that a large amount of ROS is generated after L-arg / PCN+H2O2+L treatment, which in turn damages the cells and ultimately kills the bacteria.

[0115] In summary, the nanocomposite provided by the present invention can exert a strong bactericidal effect under the conditions of hydrogen peroxide solution and light treatment, and can therefore be used in the fields of medical care and the like.

[0116] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.

Claims

1. A nanocomposite, characterized in that: The invention comprises a porphyrin metal organic framework and L-arginine loaded on the porphyrin metal organic framework.

2. The nanocomposite according to claim 1, characterized in that The particle size of the nanocomposite is 100 to 200 nm; and / or, The metal center of the porphyrin metal organic framework includes at least one of zirconium, cobalt, iron, manganese, copper, platinum and iridium; and / or, The mass percentage of L-arginine in the nanocomposite is 6.45%.

3. A method for preparing a nanocomposite according to any one of claims 1 to 2, characterized in that: The following steps are involved: The porphyrin metal organic framework, L-arginine and water are ultrasonically mixed, stirred in the dark, centrifuged to obtain solid matter, washed and dried to obtain the nanocomposite.

4. The method for preparing the nanocomposite according to claim 3, characterized in that: The step of ultrasonically mixing the porphyrin metal organic framework, L-arginine and water, stirring in the dark, centrifuging to obtain solid matter, washing, and drying to obtain the nanocomposite: The mass ratio of the porphyrin metal organic framework, L-arginine and water is 1:5:1000; and / or, The light-proof stirring time is 12 to 24 hours.

5. Use of the nanocomposite as claimed in any one of claims 1 to 2 or the nanocomposite prepared by the method for preparing the nanocomposite as claimed in any one of claims 3 to 4 in sterilization.

6. The use according to claim 5, characterized in that The following steps are involved: The nanocomposite is added into a solution to be tested, a hydrogen peroxide solution is added, and light treatment is performed to obtain a treated solution to be tested.

7. The use according to claim 6, characterized in that In the step of adding the nanocomposite to the solution to be tested, adding a hydrogen peroxide solution, and performing light treatment to obtain the treated solution to be tested: The concentration of microorganisms in the solution to be tested is less than or equal to 10 8 CFU / mL, After the nanocomplex is added into the test solution, the concentration of the nanocomplex in the test solution is 30-150 μg / mL.

8. The use according to claim 6, characterized in that In the step of adding the nanocomposite to the solution to be tested, adding a hydrogen peroxide solution, and performing light treatment to obtain the treated solution to be tested: The volume ratio of the hydrogen peroxide solution to the solution to be tested is 1:5000; The final molar concentration of hydrogen peroxide in the hydrogen peroxide solution is 100 μM.

9. The use according to claim 6, characterized in that In the step of adding the nanocomposite to the solution to be tested, adding a hydrogen peroxide solution, and performing light treatment to obtain the treated solution to be tested: The light treatment includes light treatment using visible light, and the wavelength of the visible light is 400-700nm.

10. The use according to claim 6, characterized in that In the step of adding the nanocomposite to the solution to be tested, adding a hydrogen peroxide solution, and performing light treatment to obtain the treated solution to be tested: The light treatment time is 15 to 25 minutes.